Distribution and concentration of cholesteryl ester transfer protein in plasma of normolipemic subjects. - Marcel, Y L (1990)
A MAb (TP-2) directed against human cholesteryl ester transfer protein (CETP) has been applied to the development of a competitive solid-phase RIA. Experiments with immobilized CETP have shown that upon incubation with plasma or HDL in the presence of Tween (0.05%) apo A-I (but not apo A-II) binds to CETP while TP-2 binding to CETP is concomitantly decreased. With high detergent concentration (0.5% Triton), the interference is eliminated and a specific RIA in which all plasma CETP fractions have the same affinity can be obtained. Plasma levels of CETP, apo A-I, lipids, and lipoproteins were measured in 50 normolipemic, healthy subjects of both sexes. CETP levels varied nearly fourfold with a mean value of 1.7 micrograms/ml. CETP was positively correlated only with apo A-I (r = 0.38) and HDL-triglyceride (r = 0.39). In 29 other normolipemic subjects, where several apolipoproteins were also measured, significant correlations of CETP with apo A-I (0.41), apo E (0.43), and HDL-cholesterol (0.41) were observed, but there was no significant relationship between CETP and either apo A-II, B, or D. In other experiments CETP was shown to be present mostly in HDL3 and VHDL, to display exclusively an alpha 2-electrophoretic migration, and to occur within discrete particles ranging in size from 129 to 154 kD. In conclusion, the association of CETP with apo A-I-containing lipoproteins probably explains the correlation between CETP and apo A-I levels. The relationship between CETP and apo E suggests either a common metabolism or a specific cooperative role in cholesterol ester transport for these proteins.